Biochemical assay and spectroscopic analysis of oxidative/antioxidative parameters in the blood and serum of substance use disorders patients. A methodological comparison study - Guleken, Zozan; Kuruca, Serap Erdem; Unubol, Basak; Toraman, Suat; Bilici, Rabia; Saribal, Devrim; Depciuch, Joanna (Pergamon-Elsevier Science Ltd, 2020)
Substance abuse such as opioids, cannabis, and alcohol causes activation on the immune system and the release of reactive oxygen species (ROS) into the blood and serum. These substances cause an effect on oxidant and an-tioxidant status in patients with substance abuse. Mainly, wide-open to the ROS are lipids and proteins included blood, which suffers peroxidation. In this study, for the first-time differentiation of the effects of cannabis, alcohol and other synthetic substances on blood and serum samples, were performed. For this purpose, the level of the malondialdehyde (MDA) and glutathione (GSH) in serum and red blood cells, was measured using biochemical assay methods and Fourier Transform InfraRed spectroscopy (FTIR). The results showed, that peroxidation which is dignified as the production of MDA was increased for substance use disorder (SUD) patients (18.01 +/- 2.97) compared to the control group (10.75 +/- 2.28) (p < 0.001) and for antioxidant capacity, GSH level were signifi-cantly increased for SUD patients (p < 0.001). For the discrimination of protein and lipid region obtained from FTIR spectroscopy, we extracted features by principal component analyze (PCA) of protein (1800 cm(-1) to 900 cm(-1)) and lipid (3200 cm(-1) to 2800 cm(-1)) regions for blood and serum samples collected from patients with different types of SUD and healthy control (HC) participants. For the consideration of lipid oxidation, lipid satu-ration, lipid desaturation and protein aggregation the peak heights at 1740 cm(-1) to 2960 cm(-1), 2920 cm(-1) to 2960 cm(-1), 3012 cm(-1) to 2960 cm(-1), and 1630 cm(-1) to 1650 cm(-1) regions were studied for SUD and HC. More-over, more visible changes were noticed for proteins region, than for lipids. The most notice structural changes were observed in amide II in serum spectra. Then we classified protein and lipid region's PCA results of blood and serum by Linear discriminant analysis (LDA) and Support vector machine (SVM). Confidence of the specific-ity, sensitivity and accuracy of blood and serum were obtained as 100%, 100% and 100% individually. This is the first comparative study on the spectrochemical tool and biochemical assay on SUD. Our results presented 100% discrimination of disorder region compared to healthy subjects. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Substance use disorder; FTIR; Serum; Blood; MDA; GSH